Patologi Pelayanan Publik di Era Revolusi Industri 4.0 - Hamirul, Hamirul (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2018)
This paper stems from concerns about public services available in Indonesia by using descriptive methods and qualitative approaches, the problem of existing public services in terms of pathology can be minimized in the current era of industrial revolution in view of the growing access to technology and transparency provided about the service both time and cost to be paid in terms of getting the services from the government. The type of pathology associated with perception and managerial style will be minimized by the use of technology in the service process.